Prevalence of Rheumatic Fever and Rheumatic Heart Disease in School Children of Bharateswari Homes of Bangladesh (Cardiovascular Journal, 2014)
Background: Rheumatic fever (RF) and rheumatic heart disease (RHD) continue to affect millions of people around the world, including Bangladesh. Children and adolescents are especially susceptible to this disease. Classical risk factors, i.e. poverty, overcrowding, ignorance and insufficient health care services are responsible for the high incidence and prevalence of these diseases. To assess the prevalence of RF and RHD among children, a school survey was conducted in Bharateswari Homes, in the district of Tangail, Bangladesh. Methods: A total of 947 students were examined. Revised Jones criteria (1992), and clinical examination were used for the diagnosis of RF and RHD. Results: Four cases of RF/RHD were found giving the prevalence of 4.22/1000. This is lower than the prevalence reported in eighties, but is consistent with those found in nineties. Conclusion: Among the school children, there is a declining trend in the prevalence of RF/RHD. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18348 Cardiovasc. j. 2014; 6(2): 103-106